Aderência de conjunto de dados do repositório institucional da Universidade Federal da Paraíba aos princípios FAIR - Moro, Anderson Rodrigues (2021)
The storage and availability of data in institutional repositories is a common practice in universities worldwide, as at the Federal University of Paraíba, which uses its repository for the storage of theses, dissertations, and course completion papers. As a means of providing parameters for evaluating different data sets, also applicable in repositories, the guiding principles FAIR: Findable, Accessible, Interoperable, Reusable, whose implementation strategies are supported in the GO FAIR project, which aims to provide a model for the implementation of these principles in the development of a global data interoperability infrastructure. In this context, this research aims to verify the adherence of a data set formed by the (meta)data of dissertations deposited in the Institutional Repository of the Federal University of Paraíba to the principles FAIR. To analyze this adherence, the FairDataBR tool was developed, which allows the evaluation of any data set, not being restricted to the content of institutional repositories.